Document Validation for Cooperation Agreement Documents at The Undiksha Cooperation and Public Relations Agency (Badan Kerja Sama dan Kehumasan) using Local Binary Pattern (LBP) and YOLOv5 Methods - Komang Jepri Kusuma Jaya; Made Windu Antara Kesiman; I Made Dendi Maysanjaya (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2023)
A cooperation agreement document managed by BKK Undiksha is a conventionally managed document. With the implementation of the Kampus Merdeka - Merdeka Belajar curriculum in 2021, the number of incoming cooperation agreement documents has increased rapidly, making the collection of document data much longer and inefficient. Therefore, there is a need for a scheme that can automatically validate collaboration documents. The document validation scheme was developed using the Local Binary Patterns and YOLOv5 methods. The data used in the development is primary data from BKK Undiksha in 2021, where two agencies collaborate. The development result is the document validation model collaboration using the Local Binary Pattern and YOLOv5 methods with the best accuracy results of 95.36%, and the ability of the model to detect the number of seal, stamp and signature components is 90.73%.